Kemi and Khadijat - Gomez. Aduke (Nigeria, 2022)
When talented best friends, Kemi and Khadijat find out only one of them can participate in a contest they've both been practicing hard for, they are at a loss on what to do.
Keywords: Friendship; Juvenile Fiction